2016
DOI: 10.3389/fmicb.2016.00683
|View full text |Cite
|
Sign up to set email alerts
|

Aspergillus fumigatus-Related Species in Clinical Practice

Abstract: Aspergillus fumigatus is the main etiologic agent of invasive aspergillosis (IA). Other Aspergillus species belonging to the section Fumigati (A. fumigatus complex) may occasionally be the cause of IA. These strains are often misidentified, as they cannot be distinguished from A. fumigatus by conventional morphological analysis and sequencing methods. This lack of recognition may have important consequences as these A. fumigatus-related species often display some level of intrinsic resistance to azoles and oth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
132
0
18

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 137 publications
(152 citation statements)
references
References 78 publications
2
132
0
18
Order By: Relevance
“…This finding illustrates the importance of molecular biology techniques to correctly identify the Aspergillus species of the section Fumigati, notably when the species involved are naturally resistant to azole antifungals and can be misidentified as A. fumigatus (i.e. A. lentulus) (Lamoth 2016). Although A. oerlinghausenensis has not been involved in IA in human until now, its pathogenicity requires further explorations because of its substantial presence in the environment and its resistance profile.…”
Section: Discussionmentioning
confidence: 96%
“…This finding illustrates the importance of molecular biology techniques to correctly identify the Aspergillus species of the section Fumigati, notably when the species involved are naturally resistant to azole antifungals and can be misidentified as A. fumigatus (i.e. A. lentulus) (Lamoth 2016). Although A. oerlinghausenensis has not been involved in IA in human until now, its pathogenicity requires further explorations because of its substantial presence in the environment and its resistance profile.…”
Section: Discussionmentioning
confidence: 96%
“…The most common etiological agent of invasive aspergillosis with a high morality is A. fumigatus, responsible for the majority (up to 90%) of cases in humans [1,12,[15][16][17][18][19]. It is followed by A. flavus, which causes up to 10% of cases of…”
Section: Etiology Of Invasive Aspergillosismentioning
confidence: 99%
“…Molds of the genus Aspergillus may cause a wide variety of clinical entities, ranging from asymptomatic colonization, allergic bronchopulmonary aspergillosis, and chronic pulmonary aspergillosis to severe (even fulminant) invasive infections in almost every organ or system in the body of the host, including (but not limited to) the lungs, heart, central nervous system, and the sinuses [5,18,19,24]. The most common clinical form of invasive diseases caused by Aspergillus spp.…”
Section: Clinical Forms Of Invasive Aspergillosismentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast Netherland surveillance studies showed that azole resistance is endemic, TR46/Y121F/T289A and TR34/L98H cyp51A gene mediated resistance been the most common (Van der Linden et al, 2011).Multicenter international surveillance network study reported 3.2% triazoles resistance. Majority of resistant isolates were Aspergillus species at 78% and 22% of the other sibling species (A. lentulus, A. udagawae and A. thermomutatus) (Lamoth, 2016, Van der Linden et al, 2015.…”
Section: Introductionmentioning
confidence: 99%